Heterologous Expression of AtWRKY57 Confers Drought Tolerance in Oryza sativa - Jiang, Yanjuan; Qiu, Yuping; Hu, Yanru; Yu, Diqiu (Frontiers in Plant Science, 2016)
Drought stress is a severe environmental factor that greatly restricts plant distribution and crop production. Recently, we have found that overexpressing AtWRKY57 enhanced drought tolerance in Arabidopsis thaliana. In this study, we further reported that the Arabidopsis WRKY57 transcription factor was able to confer drought tolerance to transgenic rice (Oryza sativa) plants. The enhanced drought tolerance of transgenic rice was resulted from the lower water loss rates, cell death, malondialdehyde contents and relative electrolyte leakage while a higher proline content and reactive oxygen species-scavenging enzyme activities was observed during stress conditions. Moreover, further investigation revealed that the expression levels of several stress-responsive genes were up-regulated in drought-tolerant transgenic rice plants, compared with those in wild-type plants. In addition to the drought tolerance, the AtWRKY57 over-expressing plants also had enhanced salt and PEG stress tolerances. Taken together, our study indicates that over-expressing AtWRKY57 in rice improved not only drought tolerance but also salt and PEG tolerance, demonstrating its potential role in crop improvement.